2010
DOI: 10.1038/nature09002
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin-B2 controls VEGF-induced angiogenesis and lymphangiogenesis

Abstract: In development, tissue regeneration or certain diseases, angiogenic growth leads to the expansion of blood vessels and the lymphatic vasculature. This involves endothelial cell proliferation as well as angiogenic sprouting, in which a subset of cells, termed tip cells, acquires motile, invasive behaviour and extends filopodial protrusions. Although it is already appreciated that angiogenesis is triggered by tissue-derived signals, such as vascular endothelial growth factor (VEGF) family growth factors, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
1,111
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,128 publications
(1,147 citation statements)
references
References 36 publications
31
1,111
0
5
Order By: Relevance
“…Whereas it is appreciated that directional cell migration requires trafficking of adhesion and growth factor receptors (8), including that of VEGFR2 (42,49,50), the dependence of directional migration on trafficking of cytoskeletal and motility proteins has come to light only recently. Our finding that Rab13-dependent trafficking of Syx and RhoA is required for directional cell migration resonates with a recent report on the requirement of Rab5-dependent trafficking of Rac and Tiam1 for hepatocyte growth factor-stimulated migration of mouse embryo fibroblasts (14).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas it is appreciated that directional cell migration requires trafficking of adhesion and growth factor receptors (8), including that of VEGFR2 (42,49,50), the dependence of directional migration on trafficking of cytoskeletal and motility proteins has come to light only recently. Our finding that Rab13-dependent trafficking of Syx and RhoA is required for directional cell migration resonates with a recent report on the requirement of Rab5-dependent trafficking of Rac and Tiam1 for hepatocyte growth factor-stimulated migration of mouse embryo fibroblasts (14).…”
Section: Discussionmentioning
confidence: 99%
“…25 In response to VEGFA, ephrinB2 DV MVECs were significantly less migratory than WT MVECs (Figure 5B Figure 5C). Recent studies in lung, retina, and skin 14,15 suggest that ephrinB2 is necessary for VEGFR signaling, by stimulating receptor internalization to endosomes where active signaling occurs. 26 To investigate VEGFR2 internalization in ephrinB2 DV MVECs, an "antibody feeding" assay was performed.…”
Section: Kidney Mvecs Lacking Pdz-dependent Ephrinb2mentioning
confidence: 99%
“…13 Subsequently, ephrinB2 reverse signaling was shown to regulate both developmental and tumor angiogenesis by activating vascular endothelial growth factor receptor 2 (VEGFR-2). 14,15 In separate studies, pericyte-specific ephrinB2 deficiency indicated that ephrinB2 is essential for normal coverage of the microvasculature by pericytes. 16 In these mutant mice, pericytes did not bind to ECs, resulting in microvascular hemorrhage from unstable capillaries in multiple organs such as lung and skin, leading to perinatal lethality.…”
mentioning
confidence: 99%
“…To definitively prove the role of the Wnt/b-catenin signaling pathway in the maintenance of the GVB integrity we used Cdh5(PAC)-CreERT2 mice 30 crossed with b-catenin lox(ex3)/lox(ex3) mice. 31 Crossing these mouse strains we obtained an inducible b-catenin gain-of-function mouse model in which, upon tamoxifen treatment, in VE-cadherin expressing endothelial cells exon 3 is excised from b-catenin gene and therefore it becomes constitutively active.…”
mentioning
confidence: 99%